Kondisi Kejenuhan Belajar Pada Siswa Kelas X SMA Islam Jepara - Nita Wulan Sari; Tri Suyati; Farikha Wahyu Lestari (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
This research is a study of the saturation condition of learning at Jepara Islamic High School. This study aims to determine the level of learning saturation conditions that exist in Jepara Islamic High School. This research was conducted by distributing questionnaires to be filled out by students there. The method used to analyze the data is a quantitative descriptive analysis technique which is included in the score distribution and rating scale categories that have been determined. The results of the validation of learning saturation are: (1) student learning saturation is high with a percentage of 59%. (2) student learning saturation is low with a percentage of 41%. Based on these results, the level of learning saturation of class X students at Jepara Islamic High School is in the fairly high category.